P-glycoprotein ABCB1: a major player in drug handling by mammals - Borst, Piet; Schinkel, Alfred H. (The Journal of clinical investigation, 2013)
Mammalian P-glycoproteins are active drug efflux transporters located in the plasma membrane. In the early nineties, we generated knockouts of the three P-glycoprotein genes of mice, the Mdr1a, Mdr1b, and Mdr2 P-glycoproteins, now known as Abcb1a, Abcb1b, and Abcb4, respectively. In the JCI papers that are the subject of this Hindsight, we showed that loss of Mdr1a (Abcb1a) had a profound effect on the tissue distribution and especially the brain accumulation of a range of drugs frequently used in humans, including dexamethasone, digoxin, cyclosporin A, ondansetron, domperidone, and loperamide. All drugs were shown to be excellent substrates of the murine ABCB1A P-glycoprotein and its human counterpart, the MDR1 P-glycoprotein, ABCB1. We found that the ability of ABCB1 to prevent accumulation of some drugs in the brain is a prerequisite for their clinical use, as absence of the transporter led to severe toxicity or undesired CNS pharmacodynamic effects. Subsequent work has fully confirmed the profound effect of the drug-transporting ABCB1 P-glycoprotein on the pharmacokinetics of drugs in humans. In fact, every new drug is now screened for transport by ABCB1, as this limits oral availability and penetration into sanctuaries protected by ABCB1, such as the brain.